Parametrical synthesis of the complex two-port networks for variants of their inclusion between a source of a signal and a nonlinear part by criterion of maintenance of the set characteristics amplifiers with the general feedback - Alexander A. Golovkov; Vladimir A. Golovkov (Физика волновых процессов и радиотехнические системы, 2022)
Introduction: the analysis of known literature shows that the use of various types of matching quadripoles (reactive, resistive, complex, mixed) and a feedback circuit covering a non-linear element makes it possible to increase the area of physical feasibility of given forms of frequency characteristics. The purpose of the work is to increase the area of physical feasibility of given forms of frequency characteristics by optimizing the parameters of matching complex quadripoles and using an additional feedback circuit covering a nonlinear element and a mixed quadripole. Each two-terminal network of such four-terminal networks consists of both resistive and reactive elements. Materials and methods: theory of four-terminal networks, matrix algebra, decomposition method, method of synthesis of microwave control devices, circuit engineering method for analyzing the characteristics of radio devices. Results: Mathematical models of matching complex quadripole networks are obtained in the form of relationships between the elements of their transmission matrix and the dependences of the resistances of their two-terminal circuits on frequency, which are optimal in terms of the criterion for providing specified forms of frequency characteristics. Conclusion: a comparative analysis of the theoretical results (frequency response and phase response of amplifiers) obtained by mathematical modeling in the MathCad system and experimental results obtained by circuit simulation in the OrCad and MicroCap systems shows their satisfactory agreement.